Growth and Yield Response of Soybean (Glycine max L.) in Relation to Sowing Date in the Southern Region of South Korea - Jinhee Seo; Jaesung Park; Mansoo Choi; Kiyeol Jung; Hyenchung Chun; Sanghun Lee; Donghyeok Gong; Se Eun Chae; Seung Ho Jeon; Dong-Kyung Yoon (Agronomy)
A double-cropping system is widely adopted in southern Korea, in which the sowing date of the second crop (soybean) can be delayed depending on the growth period of the first crop and weather conditions. Soybean yields may be reduced because of the shorter vegetative growth period and earlier flowering. This study examined soybean growth and yield responses as plant populations at a late planting date. A field experiment was conducted in the upland field at the Department of Southern Area Crop Science in Miryang, Gyeongsangnam-do, for two years (2022–2023) using four cultivars (Seonyu 2, Jungmo 3015, Seonpung, and Jangpung). A split-plot block design was used with three replications. The main plots had four sowing dates at 10-day intervals from 25 June to 25 July. The date of maturity was recorded, and the yield components and yield were examined after harvesting. The optimum planting population for maximizing the soybean yield with late planting was compared with the standard population result. To maintain pre- and post-crop yields and cultivate stable production, the sowing date limit for early maturing soybeans was July 15 and that for mid-maturing soybeans was July 5. The results highlight the potential to produce an economic soybean production level.